PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI PUSKESMAS GILIGENTING KABUPATEN SUMENEP - Feriyanto Ismandani; Chamariyah Chamariyah; Subijanto Subijanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
The respondents of this study were all 76 community health center staff (as a population) and 76 people were taken as the study sample; the sampling method uses Total Sampling. This type of research is explanatory research, using quantitative approaches, data analysis tools using SPSS. The research objectives are: 1) To find out the simultaneous influence of organizational culture and work motivation on the performance of staff at the Giligenting Health Center in Sumenep Regency. 2) To partially determine the effect of organizational culture and work motivation on the performance of staff at the Giligenting Health Center in Sumenep Regency. The results showed that: 1) Simultaneously, organizational culture and work motivation had a positive and significant influence on performance of staff at the Giligenting Health Center in Sumenep Regency, as evidenced by the calculated F value of 3.408 with a significant level of 0.02 ( smaller than 0.05). 2) Partially, organizational culture and work motivation have a positive and significant effect on performance of employees at Giligenting Health Center, Sumenep Regency, as evidenced by the t value of each independent variable, namely: organizational culture has a t value of 2,049 with a level of significance of 0.01 (less than 0.05) and work motivation has a calculated t value of 1.520 with a significance level of 0.02 (less than 0.05). Organizational culture has a dominant effect on performance of staff at the Giligenting Health Center in Sumenep Regency.